PLOWING DOWN HARVEST RESIDUES FROM PRECEDING CROPS FOR THE PURPOSE OF SOYBEAN YIELD IMPROVEMENT - Đukuć, Vojin H; Miladinov, Zlatica J; Dozet, Gordana K; Balešević-Tubić, Svetlana N; Miladinović, Jegor A; Ugrenović, Vladan M; Marinković, Jelena B (Journal of Agricultural Sciences (Belgrade), 2019)
Soybean yield depends on the choice of cultivar, soil fertility, cultivation practices, and weather conditions in different years. Ploughing down crops residues increases the content of soil organic matter, and thereby positively affects soil fertility. The use of crops residues as energy source has been promoted in the recent years. It would be wrong to refer to this as a renewable energy source, as removal of crops residues from agricultural fields reduces and ultimately damages soil fertility, which in turn leads to reduced yield and crops residue decrease in the future. Due to the reduced application of manure and organic fertilizers, it is necessary to return crops crop residues to the soil so as to preserve soil structure and prevent soil fertility decline. The effect of ploughing down crop residues from preceding crops on soybean yield has been the focus of studies for eleven years.  Ploughing down maize crops residues resulted in soybean yield increase by about 11,69%, i.e. the annual yield increase ranged from 2,89% to15,94%.Keywords: Crop residues, Crop rotation, Glycine max L., Yield.